2004
DOI: 10.1128/jcm.42.8.3873-3876.2004
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Porphyromonas gingivalis Biotypes Defined by Alleles of the kgp (Lys-Gingipain) Gene

Abstract: Paired subgingival plaque samples representing the most-diseased and least-diseased sites were collected from 34 adult patients with diagnosed chronic periodontitis. The percentage of Porphyromonas gingivalis relative to the total anaerobic and gram-negative bacterial load at each site was determined by real-time PCR. Based on variations in the noncatalytic C terminus of the Lys-gingipain (Kgp), it was reasoned that DNA sequence variation in the 3-coding region of the kgp gene might determine functional biotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
20
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 31 publications
(24 reference statements)
1
20
0
1
Order By: Relevance
“…Using paired subgingival samples from the most-and least-diseased sites, we showed that the majority of periodontitis patients in our study were colonized by one predominant biovar with only trace amounts of a second detectable in a few subjects. The frequency of occurrence of biovars HG66, 381, W83, and W83v was 8:11:6:5, respectively (12). In support of this observation is a recent study by Inaba and colleagues (4), who reported that fimA genotype II clinical isolates from nine Japanese periodontitis patients all possessed the HG66 biovar, while isolates from two patients corresponded to biovars 381 and W83 or biovars 381 and W83v.…”
supporting
confidence: 71%
See 4 more Smart Citations
“…Using paired subgingival samples from the most-and least-diseased sites, we showed that the majority of periodontitis patients in our study were colonized by one predominant biovar with only trace amounts of a second detectable in a few subjects. The frequency of occurrence of biovars HG66, 381, W83, and W83v was 8:11:6:5, respectively (12). In support of this observation is a recent study by Inaba and colleagues (4), who reported that fimA genotype II clinical isolates from nine Japanese periodontitis patients all possessed the HG66 biovar, while isolates from two patients corresponded to biovars 381 and W83 or biovars 381 and W83v.…”
supporting
confidence: 71%
“…However, a recent report highlights the role of gingipains and not fimbriae in preferential binding to matrix proteins, a process that could facilitate colonization of the host (9). Previously we reported that P. gingivalis could be categorized by differential PCR into four kgp biovars: HG66, 381, W83, and W83v, a domain variant of the W83 kgp gene (12). Using paired subgingival samples from the most-and least-diseased sites, we showed that the majority of periodontitis patients in our study were colonized by one predominant biovar with only trace amounts of a second detectable in a few subjects.…”
mentioning
confidence: 74%
See 3 more Smart Citations